Phenotypes Associated With MEN1 Syndrome: A Focus on Genotype-Phenotype Correlations - Mele, Chiara; Mencarelli, Monica; Caputo, Marina; Mai, Stefania; Pagano, Loredana; Aimaretti, Gianluca; Scacchi, Massimo; Falchetti, Alberto; Marzullo, Paolo (Frontiers in Endocrinology, 2020)
Multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant inherited tumor syndrome, associated with parathyroid, pituitary, and gastro-entero-pancreatic (GEP) neuroendocrine tumors (NETs). MEN1 is usually consequent to different germline and somatic mutations of the MEN1 tumor suppressor gene, although phenocopies have also been reported. This review analyzed main biomedical databases searching for reports on MEN1 gene mutations and focused on aggressive and aberrant clinical manifestations to investigate the potential genotype-phenotype correlation. Despite efforts made by several groups, this link remains elusive to date and evidence that aggressive or aberrant clinical phenotypes may be related to specific mutations has been provided by case reports and small groups of MEN1 patients or families. In such context, a higher risk of aggressive tumor phenotypes has been described in relation to frameshift and non-sense mutations, and predominantly associated with aggressive GEP NETs, particularly pancreatic NETs. In our experience a novel heterozygous missense mutation at c.836C>A in exon 6 was noticed in a MEN1 patient operated for macro-prolactinoma, who progressively developed recurrent parathyroid adenomas, expanding gastrinomas and, long after the first MEN1 manifestation, a neuroendocrine uterine carcinoma. In conclusion, proof of genotype-phenotype correlation is limited but current evidence hints at the need for long-term interdisciplinary surveillance in patients with aggressive phenotypes and genetically confirmed MEN1.